Web-Based IoT Flood Management System - Chew, Jia Xin; Mohammed Alduais , Nayef Abdulwahab (Applied Information Technology And Computer Science, 2024)
Floods can affect the economy, ecology, and human life. It will destroy crops, properties, public facilities, and other assets and cause the loss of lives. An IoT-based flood management system is a web-based system developed with PHP and MySQL. It allowed users to register multiple IoT nodes, providing a user interface to monitor the data. This system used numerous sensors to display real-time water levels, rainfall, temperature, and humidity. The collected data is sent to the system's monitoring website. The Visual Studio Code, Arduino IDE, and ThingSpeak are used as software while Arduino IDE, Arduino WeMos D1 UNO board, water level sensor (HC-SR04), temperature humidity sensor (DHT11), and rainfall sensor are hardware used to develop the system. The IoT hardware is built to test the system. Parallel development is used in this project to ensure the system is developed and functioned properly to meet the user requirements.